The cardiokine secreted Frizzled‐related protein 3, a modulator of Wnt signalling, in clinical and experimental heart failure. (9th January 2014) - Askevold, E. T.; Aukrust, P.; Nymo, S. H.; Lunde, I. G.; Kaasbøll, O. J.; Aakhus, S.; Florholmen, G.; Ohm, I. K.; Strand, M. E.; Attramadal, H.; Fiane, A.; Dahl, C. P.; et al.
Abstract Objectives Experimental studies have shown involvement of Wnt signalling in heart failure (HF). We hypothesized that secreted frizzled‐related protein 3 (sFRP3), a modulator of Wnt signalling, is related to the progression of HF. Design Circulating sFRP3 was measured in 153 HF patients and compared with 25 healthy controls. The association of sFRP3 with mortality was evaluated in 1202 patients (GISSI‐HF trial). sFRP3 mRNA expression was assessed in failing human and murine left ventricles (LV), and cellular localization was determined after fractioning of myocardial tissue. In vitro studies were carried out in cardiac fibroblasts subjected to cyclic mechanical stretch. Results (i) Heart failure patients had significantly raised serum sFRP3 levels compared with controls, (ii) during a median follow‐up of 47 months, 315 patients died in the GISSI‐HF substudy. In univariable Cox regression, tertiles of baseline sFRP3 concentration were significantly associated with all‐cause and cardiovascular mortality. After adjustment for demographic and clinical variables, but not for CRP and NT‐proBNP, the associations with mortality remained significant for the third tertile (all‐cause, HR 1.45, P = 0.011; cardiovascular, HR 1.66, P = 0.003), (iii) sFRP3 mRNA expression was increased in failing human LV, with a decline following LV assist device therapy. LV from post‐MI mice showed an increased sFRP3 mRNA level, particularly in cardiac fibroblasts, and (iv) mechanical stretch enhanced sFRP3 expression and release in myocardial fibroblasts. Conclusion There is an association between increased sFRP3 expression and adverse outcome in HF, suggesting that the failing myocardium itself contributes to an increase in circulating sFRP3.